Electrocatalytic CO2 Reduction Coupled with Water Oxidation by bi- and Tetranuclear Copper Complexes Based on di-2-pyridyl Ketone Ligand - Siyuan Yang; Tian Liu; Wenbo Huang; Chengwen Zhang; Mei Wang (Molecules)
In the field of sustainable energy conversion and storage technologies, copper-based complexes have become a research hotspot due to their efficient and stable catalytic performance. The development of bifunctional catalysts that can simplify catalytic steps, enhance efficiency, and reduce catalyst usage has become an important research area. In this study, we successfully synthesized two copper complexes with different geometries utilizing di(2-pyridyl) ketone as the ligand, [CuII2L2Cl2]·0.5H2O (1) and [Cu4IIL4(OCH3)2](NO3)2 (2) (L = deprotonated methoxy-di-pyridin-2-yl-methanol), which can serve as homogeneous electrocatalysts for water oxidation and CO2 reduction simultaneously. The turnover frequency (TOF) of complexes 1 and 2 for electrocatalytic water oxidation are 7.23 s−1 and 0.31 s−1 under almost neutral condition (pH = 8.22), respectively. Meanwhile, the TOF of complexes 1 and 2 for the catalytic reduction of CO2 to CO are 4.27 s−1 and 8.9 s−1, respectively. In addition, both complexes remain essentially unchanged during the electrocatalytic water oxidation and electrocatalytic CO2 reduction processes, demonstrating good stability. Structural analysis reveals that the distinct catalytic efficiencies originate from their geometric configurations: the binuclear structure of complex 1 facilitates proton-coupled electron transfer during water oxidation, whereas the tetranuclear architecture of complex 2 enhances CO2 activation. Complexes 1 and 2 represent the first two copper molecular electrocatalysts capable of catalyzing both water oxidation and CO2 reduction. The findings in this work can open up new avenues for the advancement of artificial photosynthesis simulation and the development of bifunctional catalysts for water oxidation and CO2 reduction.